Social Integration of Multiethnic Community of Padang City Based on Local Wisdom - Icha, Hafsyari; Moeis, Isnarmi; Indrawadi, Junaidi; Fatmariza, Fatmariza; Wirdanengsih, Wirdanengsih (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
The reason for this study was to examine the social coordination of multiethnic culture that happens amidst individuals of the city of Padang which comprises of different ethnic gatherings, societies, religions, races and nationalities. The ethnic gatherings that is occupy the city of Padang are the Minangkabau and Nias ethnic gro ups. This exploration is a subjective endlessly research information got through perception, inside and out meetings and documentation. The information were broke down through the phases of information decrease, information show and making determinations or confirmation. The legitimacy of the information was tried by utilizing the information source triangulation procedure. The consequences of the review show : 1) the type of social coordination of multiethnic networks as the premise of nearby insight in the city of Padang is found in the presence of the Nias Padang people group and the Nias Padang wedding custom. 2) the elements behind the acknowledgment of neighborhood astuteness in the social mix of the multiethnic local area of the city of Padang should be visible from verifiable variables, social variables and social elements.